2023
DOI: 10.4239/wjd.v14.i3.313
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of traditional Chinese medicine decoction for diabetic gastroparesis: A network meta-analysis

Abstract: BACKGROUND Diabetic gastroparesis (DGP) is a prevalent complication of diabetes that impairs people's quality of life and places a significant financial burden on them. The gastrointestinal symptoms of DGP patients can be improved by several Traditional Chinese Medicine (TCM) decoctions that have been shown to be effective in treating the disease. There are still many unanswered questions regarding the identification of appropriate therapeutic agents for the treatment of DGP in clinical practice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…Alternative and complementary medicines, including acupuncture and herbal supplements, have been explored, though their efficacy is not fully established[ 135 ]. These methods should complement, not replace, conventional treatments.…”
Section: Current Management and Treatment Approachesmentioning
confidence: 99%
“…Alternative and complementary medicines, including acupuncture and herbal supplements, have been explored, though their efficacy is not fully established[ 135 ]. These methods should complement, not replace, conventional treatments.…”
Section: Current Management and Treatment Approachesmentioning
confidence: 99%
“…Patients with diabetic GI disorders are treated conventionally with domperidone, metoclopramide, mosapride citrate, fiber laxatives, lactulose, polyethylene glycol and Cisapride, etc [ [3] , [4] , [5] , [6] , [7] ]. Although these western medications can reduce patients' GI symptoms, however they have certain side effects and are prone to relapse following drug discontinuation [ 8 ]. Furthermore, a considerable number of patients are not satisfied with these symptomatic treatments, therefore seeking alternative medicine is important.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that Chinese herbs were effective in the treatment of diabetic gastroparesis on clinical practice [ 8 ], and had effective in attenuating GI motility disorder in diabetic rats [ 9 , 10 ]. More recently, it has been demonstrated that Chang Run Tong (a formula of Chinese herbs) was better than Forlax to treat constipation, had better follow-up improvement after stopping drugs and no remarkably side effective was found in elderly diabetic patients [ 11 ].…”
Section: Introductionmentioning
confidence: 99%